Epidemiology of intestinal schistosomiasis in ruminants of Bangladesh (Journal of the Bangladesh Agricultural University, 2012)
We assessed the prevalence and seasonal variations of intestinal schistosomiasis in association with age, sex, breed and rearing system of cattle and goats in different districts of Bangladesh. Fecal samples from 240 cattle and 146      goats were examined. Schistosoma eggs were found in 47.5% cattle and 43.84% goats. Two species of schistosomes were identified. No mixed infection was recorded. Prevalence of Schistosoma indicum was higher in cattle (42.5%) than in goats (34.25%) whereas goats (9.59%) were more susceptible to Schistosoma spindale infection than cattle (5.0%). Age, sex, breed, rearing system and topography of the country had significant (P